REDESAIN FASILITAS KERJA YANG ERGONOMIS DENGAN MENGGUNAKAN ERGONOMIC FUNCTION DEPLOYMENT (EFD) - Amrussalam; Rahmawati; Junaedi Efendi (Jurnal Ilmiah Teknik Industri, 2023)
The goal of this research is to assess the level of hazard in the activity of grinding soybean raw materials and redesigning the work facilities ergonomically with ergonomic function deployment (EFD) in order to workers can work effectively, comfortably, safely, healthy and efficiently (ECSHE), so that the productivity of worker can increase. This research begins by conducting a task analysis on the work activities experienced by workers, conducting an ergonomic risk assessment based on the BRIEF Survey and obtaining the ergonomic redesign that ensures the product produced can truly meet the needs of workers ergonomically, by using ergonomic function deployment (EFD). The results of this reseach indicate that workers have a high level of risk caused by uncomfortable working attitudes, back, neck and arm pain, and too heavy a load. The next result is a redesign of Worker's work facilities ergonomically bu using ergonomic function deployment (EFD) with the sturdy design construction and standard materials, and design sizes based on worker dimensions, so that the worker's body posture is in a natural or normal position to provide worker comfort when carrying out activities work which includes: redesigning work facilities for milling machine & auxiliary desk, redesigning work facilities for trolleys, and redesigning work facilities for reservoirs.